Pengaruh Motivasi Belajar Dan Manajemen Diri Terhadap Prestasi Akademik Mahasiswa Prodi Administrasi Bisnis - Ika Yuanita (Jurnal Ilmiah Poli Bisnis, 2021)
The student admission system at Politeknik Negeri Padang (PNP) is divided into several systems, namelyacceptance by invitation with a quata of 30 percent, for the bidikmisi route by 40 percent, while through thePolytechnic entrance examination by 30 percent. PNP has 21 Study Programs which are spread in 7 (seven)Departments. Business Administration is a study program under the Department of Business Administration.This study aims to determine the effect of learning motivation, self-management on student academicachievement in the Business Administration , PNP. This research needs to be done to be able to evaluate thework of all elements in the PNP, especially the Business Administration Study Program. During this time inevaluating the results tend to be but we forget that input greatly affects the results. The research method usedis quantitative with online / online survey methods conducted on AB Study Program students class 2017 and2018. The results showed that self-management variables had an effect on student achievement while learningmotivation had no effect on student achievement. The limitation of this study is that it still uses variables tosee student achievement and for further research it can add other variables.